On the Education About/of Radical Embodied Cognition - Kamp, John van der; Withagen, Rob; Orth, Dominic (Frontiers in Psychology, 2019)
In mainstream or strong university education, the teacher selects and transmits knowledge and skills that students are to acquire and reproduce. Many researchers of radical embodied cognitive science still adhere to this way of teaching, even though this prescriptive pedagogy deeply contrasts with the theoretical underpinnings of their science. In this paper, we search for alternative ways of teaching that are more aligned with the central non-prescriptive and non-representational tenets of radical embodied cognitive science. To this end, we discuss recent views on education by Tim Ingold and Gert Biesta, which are based upon Dewey’s philosophy of pragmatism and Gibsons’ ecological approach. The paper starts by introducing radical embodied cognitive science, particularly as it relates to motor skill learning, one of our prime interests in research and teaching. Next, we provide a synopsis and critique of the still dominant prescriptive and explicating pedagogy of strong education. Following Ingold and Biesta, we search for a weak alternative through a careful consideration of the education of attention and the participating teacher. To illustrate our arguments, we use examples of the first author’s teaching about/of motor skill learning. The paper is concluded by briefly considering the implications of weak education for a radical embodied science of motor skill learning.